481PUpdated survival outcomes of the phase II study of low starting dose of afatinib as first-line treatment in patients with EGFR mutation-positive non-small cell lung cancer (KTORG1402). (24th November 2019) - Yokoyama, T; Yoshioka, H; Fujimoto, D; Demura, Y; Hirano, K; Kawai, T; Kagami, R; Ishida, T; Tomii, K; Akai, M; Hirabayashi, M; Nishimura, T; et al.
Abstract: Background: The phase II trial evaluated the efficacy and safety of low starting dose of afatinib in patients with advanced epidermal growth factor receptor (EGFR) mutation-positive non-small cell lung cancer (NSCLC). In primary analysis, progression free survival (PFS) met the primary endpoint. Here, we report updated survival outcomes. Methods: This study was a multi-center, single-arm, open-label phase II trial. Treatment-naïve patients with common EGFR mutation-positive NSCLC were treated with afatinib starting at a dose of 20 mg/day. If tolerated, the dose is increased by 10- mg increments up to 50mg/day. PFS and overall survival (OS) were re-evaluated at the final data cut-off point (October 2018). Results: 46 patients were enrolled. Median age was 73 years (range, 43-86). The median follow-up was 31.9 months. Median PFS of entire population was 15.2 months (95% confident interval (CI), 13.2–21.2), and 2-year PFS rate was 27.7% (95% CI, 17.1-44.7). Median OS was not estimated, and the 2-year overall survival was 76.1% (95% CI, 64.7-89.5). Performance status (PS) and existence of brain metastases at study entry were revealed to have significant impact on the survival with Cox-regression test. Among patients with disease progression on afatinib (n = 36), rebiopsy was performed on 29 patients, and T790M was proved positive on 14 patients. Twelve out of the 14 patients positive for T790M received osimertinib as a second line therapy. Median time from enrollment to progression on the osimertinib (PFS2) was 32.6 months (95%CI: 20.5-NE). Conclusions: Low starting dose afatinib therapy demonstrated promising OS outcome. PS and existence of brain metastases were predictive factors of this therapy. Clinical trial identification: UMIN 000016444. Legal entity responsible for the study: Kyoto Thoracic Oncology Research Group. Funding: Has not received any funding. Disclosure: T. Yokoyama: Honoraria (self): Boehringer Ingelheim Japan; Honoraria (self): Chugai Pharmaceutical; Honoraria (self): Taiho Pharmaceutical; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Novartis; Honoraria (self): AstraZeneca; Honoraria (self): Ono pharmaceutical; Honoraria (self): MSD. H. Yoshioka: Honoraria (self): Boehringer Ingelheim; Honoraria (self): Chugai Pharmaceutical; Honoraria (self): Taiho Pharmaceutical; Honoraria (self): Eli Lilly Japan; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Novartis; Honoraria (self): Merck Serono; Honoraria (self): Kyowa Kirin; Honoraria (self): AstraZeneca; Honoraria (self): Ono pharmaceutical; Honoraria (self): Daiichi Sankyo; Honoraria (self): MSD. D. Fujimoto: Honoraria (self), Research grant / Funding (self): AstraZeneca KK; Honoraria (self): Ono Pharmaceutical Co Lt; Honoraria (self): Bristol-Myers Squibb Co Ltd; Honoraria (self): Taiho Pharmaceutical Co ; Honoraria (self), Research grant / Funding (self): Chugai Pharmaceutical Co Ltd; Honoraria (self): MSD KK; Honoraria (self): Boehringer Ingelheim Japan Inc; Honoraria (self): Eli Lilly Japan KK. K. Hirano: Honoraria (self): Boehringer Ingelheim Japan. T. Ishida: Honoraria (self): Boehringer Ingelheim Japan. T. Hirai: Research grant / Funding (institution): Boehringer Ingelheim Japan. All other authors have declared no conflicts of interest.